Improvement in the Usability of Meat Inspection Findings for Swine Herd Health Management - Darko Maric; Sebastian Vetter-Lang; Johannes Klinger; Nikolaus Böhm; Karin Schwaiger; Annemarie Käsbohrer (Animals)
Data from post-mortem inspections conducted using official controls on the meat production of slaughtered pigs are generally considered valuable for identifying herd health issues and ensuring meat safety. However, several studies highlighted that a multi-stage assessment of lung changes would provide more useful information on animal health than the implemented binary (yes/no) recording. For this purpose, a new scheme was developed and subsequently used by trained official veterinarians at four slaughterhouses in Austria. Implementation of the multi-stage assessment was carried out in parallel with the conventional assessment, and data collected from both schemes were analyzed and compared to evaluate effectiveness. The analysis of the data (n = 20,345) showed that the most common alteration was low-grade (28.4%), followed by moderate-grade (11.3%,) and then high-grade pneumonia (5.2%). In the case of pleurisy, 88.9% of the carcasses showed no alterations of the pleura, and 11.1% had pathological changes (low-grade pleurisy = 4.7%, moderate-grade pleurisy = 2.7%, high-grade pleurisy = 3.7%). Analysis of the results showed a strong heterogeneity of the frequency of alterations between the batches reflecting various underlying animal health issues. Among the influencing factors, the origin of the pigs had the greatest influence. The project demonstrated that the new evaluation can be carried out easily with no extra time effort once staff are trained and the technological platform for reporting is adapted. The more detailed information ensures more useful feedback is provided to the farmers and supervising veterinarians, thereby ensuing animal welfare and contributing to sustainable, improved animal husbandry.